GIS based navigation system of Dhaka city - Haque, Mufti Shahriar; Biswas, Tapan (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.